Genome-wide uH2A localization analysis highlights Bmi1-dependent deposition of the mark at repressed genes. - Eric M Kallin; Ru Cao; Raja Jothi; Kai Xia; Kairong Cui; Keji Zhao; Yi Zhang (PLoS Genetics)
Polycomb group (PcG) proteins control organism development by regulating the expression of developmental genes. Transcriptional regulation by PcG proteins is achieved, at least partly, through the PRC2-mediated methylation on lysine 27 of histone H3 (H3K27) and PRC1-mediated ubiquitylation on lysine 119 of histone H2A (uH2A). As an integral component of PRC1, Bmi1 has been demonstrated to be critical for H2A ubiquitylation. Although recent studies have revealed the genome-wide binding patterns of some of the PRC1 and PRC2 components, as well as the H3K27me3 mark, there have been no reports describing genome-wide localization of uH2A. Using the recently developed ChIP-Seq technology, here, we report genome-wide localization of the Bmi1-dependent uH2A mark in MEF cells. Gene promoter averaging analysis indicates a peak of uH2A just inside the transcription start site (TSS) of well-annotated genes. This peak is enriched at promoters containing the H3K27me3 mark and represents the least expressed genes in WT MEF cells. In addition, peak finding reveals regions of local uH2A enrichment throughout the mouse genome, including almost 700 gene promoters. Genes with promoter peaks of uH2A exhibit lower-level expression when compared to genes that do not contain promoter peaks of uH2A. Moreover, we demonstrate that genes with uH2A peaks have increased expression upon Bmi1 knockout. Importantly, local enrichment of uH2A is not limited to regions containing the H3K27me3 mark. We describe the enrichment of H2A ubiquitylation at high-density CpG promoters and provide evidence to suggest that DNA methylation may be linked to uH2A at these regions. Thus, our work not only reveals Bmi1-dependent H2A ubiquitylation, but also suggests that uH2A targeting in differentiated cells may employ a different mechanism from that in ES cells.